CONTEMPORARY THOUGHT ON NINETEENTH CENTURY SOCIALISM. Volume III, Fabians, the ILP and the Labour Party - Lamb, Peter, 1960- ([S.l.] : ROUTLEDGE, 2020)
The third volume includes a range of pamphlets, lectures and other documents which help illustrate the intellectual and political activities and environment which shaped the British mainstream left of the twentieth and twenty-first centuries. The early concerns and activities of the Fabian Society since its foundation in the 1880s are illustrated in the selection, as are the concerns, problems, events and opportunities leading to the formation and early development of the Labour Party in the years from the turn of the century to the outbreak of the First World War. Also included are writings of members of the Independent Labour Party (ILP). Formed in the 1890s, the ILP not only became a key player in the formation and early development of the Labour Party but also served as a more radical alternative. The concerns and activities of these two parties and the Fabian Society overlapped one another and some of the key figures of British socialism were members of more than one of these three key organizations. As the volume illustrates, together the Fabians, ILP and Labour constituted the foundations of contemporary British social democracy.
OCLC-licensed vendor bibliographic record.
Keywords: Socialism -- Great Britain -- History -- 19th century -- Sources; HISTORY / General; HISTORY / Modern / 19th Century